Interglacial Beds at Toronto, Ontario - Karrow, Paul (Géographie physique et Quaternaire, 1990)
ABSTRACTInterglacial sediments have been known to occur at Toronto for about a century. There have been two main periods of attention: first by A. P. Coleman in the early twentieth century; and second mostly by the author and co-workers in the past quarter century. Attention was focussed early on the Don Formation because of its rich fossil assemblages. The Don Formation, consisting of gravel, sand, and clay, is commonly 6 to 9 m thick and has been encountered in outcrop only along the DonValley. However, excavations and borings indicate its presence under much of southern Metropolitan Toronto; it may continue northward along the Laurentian River Valley. Its only continuing, accessible exposure has been the Don Valley Brickyard. Early paleontological study emphasized molluscs, wood, leaves, and a few bones, which suggested a climate warmer than present. More recent studies have stressed microfossils. including pollen, diatoms, ostracodes. molluscs, Cladocera, insects, plant macrofossils, and microvertebrates. Altogether about 500 species have been identified, and the list is growing. Climatic indicators show that the Don Formation represents the declining temperatures of the waning half of an interglaciation. Although the Don Formation is beyond the range of radiocarbon dates and is undated, amino acid analysis on wood and shells support assignment to Sangamonian time. The overlying Scarborough Formation clay and sand, and the Pottery Road Formation sand contain mainly cold-climate fossils. These are in turn overlain by Early, Middle, and Late Wisconsinan tills and interbedded lacustrine sediments with corresponding radiocarbon and thermoluminescence (TL) dates.